2022
DOI: 10.3390/ijms232214197
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free DNA Fragmentomics: A Promising Biomarker for Diagnosis, Prognosis and Prediction of Response in Breast Cancer

Abstract: Identifying novel circulating biomarkers predictive of response and informative about the mechanisms of resistance, is the new challenge for breast cancer (BC) management. The integration of omics information will gradually revolutionize the clinical approach. Liquid biopsy is being incorporated into the diagnostic and decision-making process for the treatment of BC, in particular with the analysis of circulating tumor DNA, although with some relevant limitations, including costs. Circulating cell-free DNA (cf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 91 publications
0
16
0
Order By: Relevance
“…Liquid biopsy has the potential to address the identification of possible predictive biomarkers that may guide treatment decisions, monitoring of treatment response, and identification of resistance and disease recurrence. Among BC studies, fragmentomics with ctDNA and cfDI analysis have shown their role as valuable methods to extract information from the liquid biopsy with potential applications in the clinical setting from cancer detection to evaluation of treatment response and anticipation of recurrence diagnosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Liquid biopsy has the potential to address the identification of possible predictive biomarkers that may guide treatment decisions, monitoring of treatment response, and identification of resistance and disease recurrence. Among BC studies, fragmentomics with ctDNA and cfDI analysis have shown their role as valuable methods to extract information from the liquid biopsy with potential applications in the clinical setting from cancer detection to evaluation of treatment response and anticipation of recurrence diagnosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Fragmentomics in liquid biopsy has emerged as a promising approach for the detection and monitoring of cancer [ 165 , 166 , 167 , 168 , 169 ]. It involves analyzing the fragmentation patterns of cfDNA using NGS technologies (such as WES or WGS) without performing the DNA sonication step or using long-read sequencing [ 129 , 170 , 171 ].…”
Section: Emerging Methods For Liquid Biopsy Biomarker Discoverymentioning
confidence: 99%
“…This term refers to applications that characterize cfDNA fragmentation and topology patterns that mirror chromatin compaction, gene regulation and the epigenome [ 132 , 135 , 136 ]. These patterns show high specificity with respect to tissue origin and disease and are thus discussed as promising cancer biomarkers [ 137 , 138 ]. While the general feasibility of this approach has been shown for HNSCC [ 133 ], fragmentomics is still in its infancy and many technical and conceptual issues need to be resolved.…”
Section: Genetic Analysis Of Circulating Cfdna In Patients With Hnsccmentioning
confidence: 99%